2021
DOI: 10.3390/pharmaceutics13111935
|View full text |Cite
|
Sign up to set email alerts
|

Neuroinflammation as a Therapeutic Target in Retinitis Pigmentosa and Quercetin as Its Potential Modulator

Abstract: The retina is a multilayer neuronal tissue located in the back of the eye that transduces the environmental light into a neural impulse. Many eye diseases caused by endogenous or exogenous harm lead to retina degeneration with neuroinflammation being a major hallmark of these pathologies. One of the most prevalent retinopathies is retinitis pigmentosa (RP), a clinically and genetically heterogeneous hereditary disorder that causes a decline in vision and eventually blindness. Most RP cases are related to mutat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(12 citation statements)
references
References 141 publications
(180 reference statements)
0
12
0
Order By: Relevance
“…It is also worth noting that quercetin, a type of flavonoids found in CCL, has been shown to mitigate light-induced retinal degeneration in rats ( Koyama et al, 2019 ). The pharmacological potential of quercetin in attenuating neuroinflammation accompanying photoreceptor degeneration has also been demonstrated in a mouse model of RP ( Ortega and Jastrzebska, 2021 ). In addition, it has been reported that kaempferol, another flavonoid component of CCL, protects against oxidizing agent sodium iodate-induced photoreceptor degeneration ( Du et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…It is also worth noting that quercetin, a type of flavonoids found in CCL, has been shown to mitigate light-induced retinal degeneration in rats ( Koyama et al, 2019 ). The pharmacological potential of quercetin in attenuating neuroinflammation accompanying photoreceptor degeneration has also been demonstrated in a mouse model of RP ( Ortega and Jastrzebska, 2021 ). In addition, it has been reported that kaempferol, another flavonoid component of CCL, protects against oxidizing agent sodium iodate-induced photoreceptor degeneration ( Du et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…The release of inflammatory factors by injured photoreceptors and RPE may cause retinal inflammatory microenvironment and further damage the integrity of the outer retina. 32 , 33 As the presence of ORT is formed by scrolled ELM, we hypothesized that ORT may border atrophic lesions therefore isolating the local inflammatory microenvironment and thus slowing down the visual loss in late-stage BCD.…”
Section: Discussionmentioning
confidence: 99%
“…As a final measure of retinal structure following time-dependent rescue of Cngb1, we investigated the activation of Müller glia by immunolabeling glial fibrillary acid protein (GFAP) 16 . This marker indicates a retinal inflammatory response, which is present in patients with RP [17][18][19] . While this response can protect the retina from damage (e.g., by releasing neuroprotective molecules) 20,21 , prolonged activation can increase tissue damage through the release of pro-inflammatory markers 22 .…”
Section: Gliosis Present In Late Treated Retinasmentioning
confidence: 99%